The Basis of Islamic Religious Education Leadership in the Qur'an and Hadith - Jaeni MJ; Romlah Abu Bakar Askar; Munzir Suparta (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
This study discusses the basis of leadership in Islamic religious education taken from the Qur'an and Hadith. Leadership in the context of religious education has an important role in shaping the character and morals of students. The Qur'an emphasizes that leaders must be just, wise, and responsible. In Surah Al-Baqarah verse 30, Allah SWT states that humans are made as caliphs on earth, which requires each individual to lead with full responsibility and carry out the mandate. In addition, the Hadith of the Prophet Muhammad SAW also provides concrete examples of good leadership, such as in managing community affairs and education. The Prophet said, "Each of you is a leader, and each of you will be held accountable for those he leads." Through this study, it was found that the basis of leadership in Islamic religious education is not only focused on the intellectual aspect, but also includes spiritual and moral dimensions. Therefore, it is important for educators to internalize the leadership values ​​contained in the Qur'an and Hadith in order to create a generation that is not only academically intelligent but also has noble morals. This study is expected to provide a contribution to the development of religious education leadership based on Islamic values.